2022
DOI: 10.1136/bmjopen-2021-049821
|View full text |Cite
|
Sign up to set email alerts
|

Clinical perspectives on the identification of neurodevelopmental conditions in children and changes in referral pathways: qualitative interviews

Abstract: ObjectivePrevious work has raised questions about the role of general practitioners (GPs) in the identification of neurodevelopmental conditions such as autism spectrum disorders (autism) and attention deficit hyperactivity disorders (ADHD). This study aimed to explore how GPs identify these conditions in practice and their perspectives on recent changes to local referral pathways that mean referrals to the neurodevelopmental team come through educational professionals and health visitors, rather than GPs. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Findings regarding assessment practices, referral pathways and differential diagnosis are presented elsewhere. [20][21][22] The findings presented in the current article focus exclusively on participants understanding of the experiences of parents.…”
Section: Methodsmentioning
confidence: 99%
“…Findings regarding assessment practices, referral pathways and differential diagnosis are presented elsewhere. [20][21][22] The findings presented in the current article focus exclusively on participants understanding of the experiences of parents.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, clinicians indicated that a vignette of a complex case would lead them to consider a number of possible diagnoses, assessments, and support services for children both 4-and 8-years of age. The response to the vignettes corroborate previous research that referral descriptions of multiple neurodevelopmental conditions suggests case-complexity and do not result in a universal pathway to assessment and management (Coughlan et al, 2022;Male et al, 2020). The pressure to diagnose neurodevelopmental conditions quickly and accurately stems from the mounting evidence for impact of early diagnosis and support on life outcomes (Whitehouse et al, 2021).…”
Section: Discussionsupporting
confidence: 65%
“…Several studies with other professionals have noted limitations with the CAMHS model and commissioning practices particularly pertaining to diagnostically oriented pathways, unclear eligibility criteria and long waiting times (e.g., Ani et al, 2022; Coughlan et al, 2022; Godar, 2017). In general, there was a sense that psychologists in this study were cognisant and sympathetic to these critiques of CAMHS.…”
Section: Discussionmentioning
confidence: 99%